Pavlovian‐to‐instrumental transfer effects in the nucleus accumbens relate to relapse in alcohol dependence. (1st April 2015) - Garbusow, Maria; Schad, Daniel J.; Sebold, Miriam; Friedel, Eva; Bernhardt, Nadine; Koch, Stefan P.; Steinacher, Bruno; Kathmann, Norbert; Geurts, Dirk E. M.; Sommer, Christian; Müller, Dirk K.; Nebe, Stephan; et al.
Abstract: In detoxified alcohol‐dependent patients, alcohol‐related stimuli can promote relapse. However, to date, the mechanisms by which contextual stimuli promote relapse have not been elucidated in detail. One hypothesis is that such contextual stimuli directly stimulate the motivation to drink via associated brain regions like the ventral striatum and thus promote alcohol seeking, intake and relapse. Pavlovian‐to‐Instrumental‐Transfer (PIT) may be one of those behavioral phenomena contributing to relapse, capturing how Pavlovian conditioned (contextual) cues determine instrumental behavior (e.g. alcohol seeking and intake). We used a PIT paradigm during functional magnetic resonance imaging to examine the effects of classically conditioned Pavlovian stimuli on instrumental choices in n = 31 detoxified patients diagnosed with alcohol dependence and n = 24 healthy controls matched for age and gender. Patients were followed up over a period of 3 months. We observed that (1) there was a significant behavioral PIT effect for all participants, which was significantly more pronounced in alcohol‐dependent patients; (2) PIT was significantly associated with blood oxygen level‐dependent (BOLD) signals in the nucleus accumbens (NAcc) in subsequent relapsers only; and (3) PIT‐related NAcc activation was associated with, and predictive of, critical outcomes (amount of alcohol intake and relapse during a 3 months follow‐up period) in alcohol‐dependent patients. These observations show for the first time that PIT‐related BOLD signals, as a measure of the influence of Pavlovian cues on instrumental behavior, predict alcohol intake and relapse in alcohol dependence. Abstract : To date mechanisms by which contextual stimuli promote relapse in detoxified alcohol‐dependent patients have not been elucidated. One hypothesis is that contextual stimuli stimulate the motivation to drink (Pavlovian‐to‐Instrumental‐Transfer; PIT) via associated brain regions like the ventral striatum and thus promote relapse. Using a PIT paradigm during fMRI, we observed that PIT‐related Nucleus Accumbens activation was associated with and predictive of relapse during a three months follow up period in detoxified alcohol‐dependent patients.